Analysis of the level of human resources competence in the implementation of digital transformation - Syahputra, Zulfausi Wahyu; Fitrianingsih, Julia; Jalal, Jalal (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction:In the era of Industry 4.0, digital transformation has become a necessity for organizations to remain competitive. However, the success of digital transformation initiatives is highly dependent on the competence of human resources (HR). This study aims to analyze the level of HR competence and its influence on the effectiveness of digital transformation implementation. Research Methodology:This research employs a quantitative descriptive method using survey data collected from 150 employees across various departments in a mid-sized enterprise undergoing digital transformation. The data were analyzed using statistical tools to measure the correlation between HR competence indicators and digital transformation progress. Result: Findings indicate that 68% of the workforce possesses basic digital skills, while only 24% demonstrate advanced digital and analytical capabilities. Departments with higher digital competence reported smoother transitions and better performance metrics post-transformation. Conclusion: The level of HR competence plays a critical role in the success of digital transformation. Organizations must invest in continuous training and development to bridge the competency gap and support a sustainable digital shift